Soft tissue injuries: Chapter 8 Forearm, hand and wrist. Issue 2 (15th February 2010) - Southern, Stephen; Sloan, John
Abstract : Hand, wrist and forearm injuries are common presentations to the emergency department. There is a huge variation of severity from small lacerations involving only skin to extensive upper limb composite loss. There is no minor injury in upper limb trauma. Even the most trivial of wounds may be associated with major tendon or nerve damage which, if missed, may have life-long functional implications for the patient. Although this review concentrates on soft tissue injury and not bony injury, it is not possible to separate the two completely. It is important to realise that all fractures have a soft tissue injury component that needs to be assessed and correctly treated. In some instances the soft tissue component is much more important than the fracture, and failure to recognise it will result in a poor outcome.